Treatment of Recurrent Intracranial Aneurysms: Gore-Tex Interposition Method for Prevention of Galvanic Corrosion at the Clips - Yokoya, Shigeomi; Hino, Akihiko; Oka, Hideki (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
We describe a new method for preventing galvanic corrosion induced by contact between old and new clips of different materials during clipping for recurrent intracranial aneurysms. After applying a new clip to the aneurysm neck close to the old clip, a Gore-Tex (GORE PRECLUDE; W.L. Gore & Associates, Inc., Newark, Delaware, United States) sheet is interposed to prevent contact between the old and new clip. The procedure was used successfully in three cases. The present technique is beneficial for the treatment of recurrent intracranial aneurysms to prevent galvanic corrosion when encountering difficulty in removing a previously placed clip.
Keywords: galvanic corrosion; recurrent aneurysms; different materials; Gore-Tex sheet